Addressing Parental Smoking in Pediatric Settings of Chinese Hospitals: A Qualitative Study of Parents - Abdullah, Abu S. (Hindawi Publishing Corporation, 2014)
This study explored factors associated with SHS exposure from parental smoking in Chinese families and assessed nature of antismoking discussions parents had with their children's pediatricians and how pediatricians might best engage with parents in an effort to reduce children's exposure to SHS. Six focus group discussions (FGDs) were conducted among 33 Chinese parents attending six major hospitals in Guangxi province, China. Most participants (32/33) had family members who smoke, and only 21% had strict restriction on smoking at home. Some parents did not know about health consequences of smoking and effects of SHS exposure on children. Situations that made it especially hard to avoid the child's SHS exposure were having an elderly smoker at home and having a visitor who smoked. Only few parents were asked by pediatricians about child's exposure to SHS at home, but only when child's illness was related to smoking. Parents believed that suggestions coming from pediatricians about smoke-free home and parental quitting would be acceptable to parents and other household members. The findings provide insight into SHS exposure reduction effort among Chinese parents and underscore the demand for pediatrician's engagement in addressing parental tobacco use.